APPLICATION INTERACTIVE TOURISM OF BANDA ACEH CITY USING ADOBE FLASH CS6 - Farhansyah, Atras; Muttaqin, Muttaqin (Ubudiyah Indonesia University, 2016)
Development of multimedia makes the delivery of information becomes more practical. Banda Aceh is a city that has tourism potential which is a relic of history. The problem is the media to promote the tourist attractions and historic sites is not maximized. For that created an interactive application that contains information on tourism in the city of Banda Aceh. In scientific writing, create interactive applications Banda Aceh tourism using Adobe Flash CS6. This application is interactive in which the user can choose the location where you want to know. The interactive application is also accompanied by a minimalist travel map containing tourist sites. It also added amenities of the town and a glimpse of information contains the address of the tourist attractions. Output is later is a file-based application exe (Execute) file and swf (Small Web Format) files which contains information on tourism sites in Banda Aceh. Output of the file will be saved in the long term and more practical. This application is expected to be used by the people of Banda Aceh to promote tourist places in the city. With the media is also expected to foster community interest outside Banda Aceh to visit attractions in the city of Banda Aceh.Keyword : Media Information, Tourism, Multimedia, Interactive Application.